Endoscopic ultrasonography as additional preoperative workup is valuable in half of the patients with a pancreatic body or tail lesion - Janssen, Quisette P; Gorris, Myrte; van den Broek, Bram L J; Besselink, Marc G; Busch, Olivier R; van Eijck, Casper H J; Groot Koerkamp, Bas; van Hooft, Jeanin E; van Driel, Lydi M J W (HPB (Oxford, England), 2022)
The management of pancreatic body and tail lesions is underexposed. It remains unclear whether endoscopic ultrasonography (EUS) increases the accuracy of the preoperative workup. This study assessed the diagnostic value and safety of EUS in addition to cross-sectional imaging in a surgical cohort of patients with pancreatic body or tail lesions. A multicenter retrospective cohort study was performed of patients who underwent distal pancreatectomy from 2010 to 2017. The composite primary outcome was the additional value of EUS, defined as: (a) EUS confirmed an uncertain diagnosis on cross-sectional imaging, (b) EUS was correct in case of discrepancy with cross-sectional imaging, or (c) EUS provided tissue diagnosis for neoadjuvant treatment. Furthermore, serious adverse events and needle tract seeding were assessed. In total, 181 patients were included, of whom 123 (68%) underwent EUS besides cross-sectional imaging. Postoperative pathology was heterogeneous: 91 was malignant, 49 premalignant, 41 benign. Most lesions were solid (n = 117). EUS had additional value in 59/123 (48%) patients; 27/50 (54%) of cystic and 32/73 (44%) of solid lesions. No serious adverse event or needle tract seeding following EUS occurred. EUS had additional value besides cross-sectional imaging in half of the patients and showed low associated risks.